Safe haven assets in emerging market (evidence from gold, government bonds, and crude oil in Indonesia 2019 – 2024) - Hapsari, Yudith Dyah; Hamid, Agustini (Trigin Publisher, 2026)
The study investigates the Save Haven properties of Gold, West Texas Intermediate (WTI) Crude Oil and Indonesian Government Bonds with maturities of 5 and 10 years against the Indonesian stock market over the period 2019 – 2024. The period encompasses episodes of global financial stress, the COVID-19 pandemic, post-pandemic recovery, and heightened geopolitical and macroeconomic uncertainty from 2019 to 2024. Understanding safe-haven assets is crucial for investors in the Indonesian stock market, especially during periods of market turbulence. This study examines the characteristics of these assets, their link with geopolitical factors and economic stability, the influence of foreign exchange rates, and the function of diversification strategies in risk mitigation. We applied quantile regression method processed to evaluate relationship across different points of the return distribution. The results indicate that gold functions as a conditional safe-haven asset in Indonesia. Government bonds 5 years and 10 years demonstrate a maturity-dependent safe-haven attribute. Conversely, WTI crude oil serves as a significant safe haven predominantly in the later segments of the sample, notably in 2023 and 2024, while exhibiting minimal safe-haven characteristics during the initial periods. Overall, the results underscore the inherently dynamic and asset-specific nature of safe-haven effectiveness in emerging markets, demonstrating that no single asset consistently provides protection across all market scenarios in Indonesia